Lumbar spine angles and intervertebral disc characteristics with end-range positions in three planes of motion in healthy people using upright MRI. (24th May 2019) - Berry, David B.; Hernandez, Alejandra; Onodera, Keenan; Ingram, Noah; Ward, Samuel R.; Gombatto, Sara P.
Abstract: Understanding changes in lumbar spine (LS) angles and intervertebral disc (IVD) behavior in end-range positions in healthy subjects can provide a basis for developing more specific LS models and comparing people with spine pathology. The purposes of this study are to quantify 3D LS angles and changes in IVD characteristics with end-range positions in 3 planes of motion using upright MRI in healthy people, and to determine which intervertebral segments contribute most in each plane of movement. Thirteen people (average age = 24.4 years, range 18–51 years; 9 females; BMI = 22.4 ± 1.8 kg/m 2 ) with no history of low back pain were scanned in an upright MRI in standing, sitting flexion, sitting axial rotation (left, right), prone on elbows, prone extension, and standing lateral bending (left, right). Global and local intervertebral LS angles were measured. Anterior-posterior length of the IVD and location of the nucleus pulposus was measured. For the sagittal plane, lower LS segments contribute most to change in position, and the location of the nucleus pulposus migrated from a more posterior position in sitting flexion to a more anterior position in end-range extension. For lateral bending, the upper LS contributes most to end-range positions. Small degrees of intervertebral rotation (1–2°) across all levels were observed for axial plane positions. There were no systematic changes in IVD characteristics for axial or coronal plane positions.